Functional Status Is Associated With Prefrontal Cortex Activation in Gait in Subacute Stroke Patients: A Functional Near-Infrared Spectroscopy Study - Hermand, Eric; Compagnat, Maxence; Dupuy, Olivier; Salle, Jean-Yves; Daviet, Jean-Christophe; Perrochon, Anaick (Frontiers in Neurology, 2020)
The increasing of cerebral oxygenation, more precisely the overactivation of the prefrontal cortex (PFC), reflects cortical control of gait in stroke disease. Studies about the relationship between brain activation and the functional status in stroke patients remain scarce. The aim of this study was to compare brain activation, gait parameters and cognitive performances in single and dual tasks according to the functional status in subacute stroke patients. Twenty-one subacute stroke patients were divided in two groups according to Barthel Index (‘Low Barthel’ and ‘High Barthel’) and performed randomly ordered walking, cognitive task (n-back task) and dual tasks (walking + n-back task). We assessed gait performances (speed, variability) using an electronic walkway system and cerebral oxygenation (∆O2Hb) by functional near infrared spectroscopy. Patients with better functional status (‘High Barthel’) showed a lower PFC activation (∆O2Hb) and better gait parameters in single and dual-tasks compared to ‘Low Barthel’ patients, who exhibited decreased gait performances despite a higher PFC activation, especially in the unaffected side (P<0.001). PFC overactivation in less functional subacute stroke patients may be due to the loss of stepping automaticity. Our results underline the interest of proposing rehabilitation programs focused on walking, especially for patients with low functional capacity.